Aeolian sediment transport on a recovering storm‐eroded foredune with sand fences. Issue 6 (26th January 2018) - Jackson, Nancy L.; Nordstrom, Karl F.
Abstract: Studies of sediment transport on developed coasts provide perspective on how human adjustments alter natural processes. Deployment of sand‐trapping fences is a common adjustment that changes the characteristics of the dune ramp and its role in linking sediment transfers from the backshore to the foredune. Fence effects were evaluated in the field using anemometer arrays and vertical sediment traps placed across a beach and dune at Seaside Park, New Jersey, USA during onshore and longshore winds. The foredune is 18 m wide and 4.5 m above the backshore. The mean speed of onshore winds at 0.5 m elevation decreased by 17% from the berm crest to the upper ramp and 36% in the lee of a fence there. Sediment transport during mean wind speeds up to 8.0 m s −1 at 0.5 m elevation was < 0.06 kg m −1  h −1 on the berm crest and backshore where fetch distances were < 45 m and surface sediment was relatively coarse (0.74–0.85 mm) but increased to 5.63 kg m −1  h −1 on the upper ramp aided by the longer fetch distances (up to 82 m) and finer grain size of the source sediment there (0.52 mm). Sediment transport along the berm crest and backshore during longshore winds, where fetch distances were > 200 m, was up to 58.69 kg m −1  h −1, about three orders of magnitude greater than during the onshore winds. Fences can displace the toe of the ramp farther seaward than would occur under natural conditions. They can create a gentler slope and change the shape of the ramp to a more convex form. A fence on the ramp can cut off a portion of sediment supply to the upper slope. Decisions about fence placement thus should consider these morphologic changes in addition to the effects on dune volume. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Effects of fence placement on dune ramp development and sediment transport to the foredune are investigated during onshore and longshore winds on a developed shoreline. Fences can displace the ramp toe seaward, change the slope and shape of the ramp, create a new zone of flow stagnation higher on the dune, and restrict sediment supply to the upper slope.